KAJIAN YURIDIS TERHADAP PRAKTIK LEGAL DRAFTING PERATURAN DESA DI INDONESIA - Mardona Siregar (Yurisprudentia: Jurnal Hukum Ekonomi, 2015)
Village autonomy momentum has been reshuffeld for three times during 2005, the firs reshuffele is the constitution No. 32 in 2004, the second is the constitution No. 23 in 2014. the latest constitution is about village regulation realigus the implementation of regional policy to be more representative and accountable towards democracy establish ment od local politic. of cours, the village area will has more chancesw in improping regional creativity in creating the aims of village establishment. because of the cultural deversity  in Indonesia the govermnet try hard to make commonn regulation. by this admission the goverment gives a great deal of authority to the village apparatur to make local regulation. the problem of the this study is hoe to implement the legal drafting ptactice of village regulaton in Indonesia. the method of this study was by applying law writing method that is yuridis normative, whic. th revewing the regulations linked to the theory ysed to analize the problem. the result of this study is one of the thypical of indonesia lies in the cultural divesity, language, religion, tribe and so on. so that, Bhineka Tunggal Ika become and exactt expressionnto the Indonesian citizen. althought the village regulation in the constitution no. 12 in 2011 explais unclear village regulation formation can be done mutatiscally and mutandiscally. the village regulation formation can not be separated fro the society as the stake holder. sothat, in village  governnut concil wich legislatively handle the regulation.